The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1535370216665173
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Evaluation of pulmonary response to inhaled tungsten (IV) oxide nanoparticles in golden Syrian hamsters

Abstract: Extensive industrial and military uses of tungsten have raised the possibilities of human occupational and environmental exposure to nanoparticles of this metal, with concomitant health concerns. The goal of this study was to investigate the potential mechanism of pulmonary toxicity associated with inhaled tungsten (IV) oxide nanoparticles (WO NPs) in Golden Syrian Hamsters. Animals exposed to WO NPs via inhalation were divided into three groups - control and two treatment groups exposed to either 5 or 10 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Considering this increased concentration, the risk of inhalation or contamination with these nanoparticles is high. Increased tungsten use could lead to contamination of air, water, and soil near tungsten mines or industrial sites [13]. In speciality studies, exposure of W particles has been shown to have no adverse effect at a concentration of up to 100 μg/mL, and the toxic effect is significant at a concentration of at least 250 μg/ mL [1].…”
Section: Toxicology Studies Devoted To Tungsten At Micro-and Nanoscalementioning
confidence: 99%
“…Considering this increased concentration, the risk of inhalation or contamination with these nanoparticles is high. Increased tungsten use could lead to contamination of air, water, and soil near tungsten mines or industrial sites [13]. In speciality studies, exposure of W particles has been shown to have no adverse effect at a concentration of up to 100 μg/mL, and the toxic effect is significant at a concentration of at least 250 μg/ mL [1].…”
Section: Toxicology Studies Devoted To Tungsten At Micro-and Nanoscalementioning
confidence: 99%
“…forms. Experimental studies have demonstrated an increase in inflammation and oxidative stress processes as well as histological impairments in rodent lungs after exposure of upper airways to tungsten (Roedel et al, 2012;Prajapati et al, 2017). Very recently, using two in vitro models, BEAS-2B cells and 3D human airway epithelium model, differential responses to tungsten were documented: epigenotoxic alterations and transient inflammatory response (George et al, 2019;Uboldi et al, 2019).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The broad use of MoO 3 NPs raises a concern of possible adverse health effects in humans as various metal nanoparticles such as tungsten oxide, cobalt oxide, lanthanum oxide, cerium oxide, and carbon nanotubes have been associated with accumulation in tissues and tissue injury. 610 Although respiratory exposure to MoO 3 NPs has not been thoroughly studied, the inhalation of Mo compounds has been shown to result in irritation to the respiratory tract, pulmonary hemorrhages, perivascular edema, and damage to the liver and kidneys. 11 A long-term study of occupational exposure to Mo fumes containing MoO 3 has indicated that concentrations between 1 and 19 mg/m 3 resulted in the development of pneumoconiosis.…”
Section: Introductionmentioning
confidence: 99%
“…16 Golden Syrian Hamsters have been used as models of lung diseases such as pulmonary fibrosis, emphysema, and acute lung injury. 6,17,18 More recently, this animal model has been used to study the sex differences following infection to SARS-CoV-2, along with the development of acute respiratory distress syndrome. 19,20…”
Section: Introductionmentioning
confidence: 99%